Influencia de la educación diabetológica en el control metabólico de las personas portadoras de diabetes mellitus tipo 2, que conformas la junta de agua potable del barrio Suanamaca, parroquia Chile, cantón Calvas, durante el periodo de noviembre 2012 a noviembre 2013 - Rodríguez Bravo, Yuliana Sthefanía (2014)
The American Diabetes Association (ADA) and the American Diabetes Association (ALAD) have stated that "Education is a right of every diabetic patient" and should be part of treatment in all health systems, both public and private. This research's main objective is to identify the influence of diabetes education on metabolic control of diabetic patients of the board of potable water Suanamaca neighborhood. It is a descriptive cross-sectional study. It was applied to 87 People With Diabetes Mellitus Type 2, 55 people attended the diabetes education and 32 did not. The educational plan was performed for eight months and tests basal glucose and glycated hemoglobin A1c at baseline and at the end of it. It was concluded that those who attended the educational plan had better metabolic control, most decreased basal glucose values below 140 mg/dL and glycated hemoglobin A1c in the range of 7%. Compared with those who did not attend diabetes education basal glucose values >140mg/dl and glycosylated hemoglobin A1c in the range of 7%, no variation, indicating an inadequate metabolic control remained. A large part of the population is obese, sedentary is no evidence of diabetic nephropathy and the majority of the population has diabetic peripheral neuropathy. This study aims to contribute to approach diabetes education programs to provide the patient with information and training needed to take responsibility for managing your illness and thus achieve good metabolic control, prevent complications, and maintain or improve quality of life . Keywords: Metabolic control, glucose, glycosylated hemoglobin A1c.